Analysis Of The Factors Affecting The Semiconductor Manufacturing System Using Simulation Based Modelling - Zul Zaffri, Mustafa (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Semiconductor is made of monocrystalline silicon as the primary material that can be used for the manufacture of a semiconductor device. For the sake of existence and succeed on a global market, manufacturing companies need to be imaginative in delivering revolutionary and superior goods with short running times and competitive rates in order to achieve operational efficiencies, such as reliability, cost, distribution and versatility, must always fulfil their specifications (Eng, K. & Choi, K., 2016). The main idea of this study is to develop and analyse the simulation model of semiconductor manufacturing process. The objective of this study is to develop a simulation model based on the conceptual model of the semiconductor production. In addition, by using the experiment model, the factors number of curing machine, percentage rate rejection of frame at curing process and number of clip bond machine were investigated to study their effect on system performance parameters. The production output and production time of semiconductor are the main factors that determine the capability of semiconductor plant. Therefore, the data of production were collected from AMKOR Technology Malaysia Sdn. Bhd located at the Telok Panglima Garang, Selangor. Based on the data collected, a conceptual model is developed based on the process flow in the plant before converting it into simulation model in ARENA platform. The simulation model was further verified, determination of warm-up period, validated and experimented. The results from the ., experiment study were collected according to design of experiment (DOE). Then, ANOV A analysis was conducted to compare the main effect and the interaction between the factors. The sensitivity analysis was carried out on the simulation model to see whether system performance parameter is sensitive towards the change in system variables. The main findings are discussed and interpreted on the basis of the data collection derived from the simulation model. The factor number of curing machine shows that production cycle time and production quantity not changed. Factor percentage rejection frame at curing process, the cycle time of the manufacturing process is no changed, but the quantity output was decreased continuously. Finally, factor number of clip bond machine increased, the time of the production cycle is remained no change and the quantity of production inconsistently increased.